78 INHIBITING GLUCONEOGENESIS PREVENTS THE EFFECTS OF FREE FATTY ACIDS ON GLUCOSE EFFECTIVENESS. (1st March 2006) - Koppaka, S.; Lee, D. E.; Kishore, P.; Tonelli, J.; Hawkins, M.
Abstract : Glucose effectiveness, the ability of hyperglycemia to suppress endogenous glucose production (EGP), is lost in type 2 diabetes mellitus (T2DM). Free fatty acids (FFA) modulate the effectiveness of glucose to suppress EGP, and increased FFA contribute importantly to the loss of glucose effectiveness in T2DM. Elevating FFA levels in nondiabetic subjects increases gluconeogenesis (GNG) and impairs glucose effectiveness. However, inhibiting GNG alone does not decrease EGP under normoglycemic conditions because of compensatory increases in glycogenolysis (autoregulation). Since hyperglycemia inhibits glycogenolysis, we hypothesized that inhibiting GNG in the presence of hyperglycemia would decrease EGP and prevent the negative impact of FFA on glucose effectiveness. To determine the impact of inhibiting GNG in the presence of elevated FFA, EGP ([3-3H]-glucose) was measured during three separate 7h normoglycemic/hyperglycemic 'pancreatic clamp' studies in n = 7 nondiabetic subjects (1F/6M; age = 45 ± 5 years; BMI = 28 ± 3.0 kg/m 2 ). Following an initial 210-minute interval of euglycemia (5 mM), blood glucose levels were raised to hyperglycemic levels (10 mM) from t = 210-420 minutes. The first pancreatic clamp study was a baseline study with saline infusions (Lip2/Et2) in which hyperglycemia suppressed EGP by 61%. Lipid emulsion (Liposyn 20%) was infused throughout the second and third study types (Lip+ and Lip+/Et+) to increase FFA to T2DM levels (Å500 mM). After raising plasma FFA to T2DM levels, suppression of EGP by hyperglycemia was impaired in Lip+ (34% suppression) and rates of GNG increased by 67% to 1.49 ± 0.14 mg/kg.min ( p = .03). In addition to Liposyn, ethanol (Et) was infused during hyperglycemia in the third study type (Lip+/Et+) to rapidly inhibit GNG (measured by deuterated water) by {223}80%. GNG inhibition significantly enhanced suppression of EGP by hyperglycemia (65.8% decrease, p = .004 vs Lip+) and thus restored glucose effectiveness ( p = .6 vs Lip2/Et2). We conclude that increased FFA impair the ability of glucose to suppress EGP in large part due to FFA-induced stimulation of GNG. Inhibiting GNG with ethanol restored glucose effectiveness despite increases in FFA up to T2DM levels. Thus, inhibiting GNG is a potential approach to regulate glucose production in T2DM.